DOI: 10.24834/isbn.9789186295899
|View full text |Cite
|
Sign up to set email alerts
|

Med uppdrag att dokumentera de yngsta barnens lärande : en verksamhetsteoretisk analys av förskolors dokumentation

Abstract: Titel:Med uppdrag att dokumentera de yngsta barnens lärande. En verksamhetsteoretisk analys av förskolors dokumentation Författare:Ann-Charlotte Lindgren Språk:Svenska med engelsk sammanfattning Nyckelord:Förskola, dokumentation, yngre barns lärande, arbetslag, verksamhetssystem, centrala handlingar, motsättningar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 34 publications
(100 reference statements)
0
3
0
7
Order By: Relevance
“…To allow for an overview and analysis of the topics, I inductively named and coded all topics, and then clustered and categorised them until I found that they formed cohesive categories, inspired by "grounded theory" and the "constant comparative method" (Glaser & Strauss 1967;Lindgren 2014b;Lindgren 2020). This yielded ten main topic categories, reflecting the main forest conflicts present in the material, which were: i. energy, ii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To allow for an overview and analysis of the topics, I inductively named and coded all topics, and then clustered and categorised them until I found that they formed cohesive categories, inspired by "grounded theory" and the "constant comparative method" (Glaser & Strauss 1967;Lindgren 2014b;Lindgren 2020). This yielded ten main topic categories, reflecting the main forest conflicts present in the material, which were: i. energy, ii.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, my analysis of the materials has mainly been data-driven, starting with participants' statements and the general themes and ideas they reflect. The processing of the material has been inspired by grounded theory and the constant comparative method (Glaser & Strauss 1967;Lindgren 2014b;Thornberg & Forslund Frykedal 2019), and it included the following steps: i. transcription of the material; ii. coding of statements; iii.…”
Section: Materials and Analysismentioning
confidence: 99%
“…Det övergripande syftet med denna artikel är att undersöka vilka iakttagelser nio elever i årskurs 4 gör när de läser berättelsen "Draken med de röda ögonen" (Lindgren, 1980) och diskutera dessa ur ett didaktiskt perspektiv. Forskningsfrågorna lyder:…”
Section: Syfteunclassified
“…Trots att den såväl innehållsligt som formmässigt kan ge associationer till Lindgrens författarskap hör den till hennes mindre kända berättelser. 5 I studien används den version som finns i antologin Sagorna (Lindgren, 1980). I korthet handlar berättelsen om två syskon på en bondgård som en morgon i april upptäcker att deras sugga har fött tio smågrisar -och en drake!…”
Section: Materials Och Metodunclassified
See 1 more Smart Citation